Employee participation and carbon emissions reduction in Australian workplaces. Issue 2 (19th January 2016) - Markey, Raymond; McIvor, Joseph; Wright, Chris F.
Abstract : This paper addresses a research gap on the role of employee participation in motivating workplace climate change mitigation activities. Drawing upon a survey of 682 Australian employers and an analysis of 1329 enterprise agreements, we find strong associations between organisational activities for the reduction of carbon emissions and employee participation in motivating, developing and/or implementing these measures. Engagement with emissions reduction at the workplace level is more likely where employee participation has a substantive role involving deeper and wider influence in organisational decision-making. This is especially the case when a range of approaches, including collective bargaining through trade unions, are utilised. Reflecting extant research on employee participation, this study confirms the importance of the concepts of depth and scope in evaluating the extent to which employee participation is substantive, and that different forms of participation have mutually reinforcing impacts over workplace decisions to reduce carbon emissions. The findings presented suggest that the form of participation may be less important than the way in which it is implemented and the degree of substantive influence that employees have in practice.